The psychological security level and academic achievement of selected high school students from father-absent and father-present families of Canossian schools SY 1990-1991 : a comparative study - Salvosa, Noraida Glorioso (Animo Repository, 1992)
This study dealt with the psychological security level and academic achievement of students of Canossa schools whose fathers were either present or absent from home by reason of work abroad. The researcher intended to find out whether father presence or absence was an important factor in the psychological security level and academic achievement of the students. The major hypothesis of the study was that there is a significant difference between presence or absence of the father and the student's psychological security level and academic achievement. Furthermore, that gender and absence or presence of the father have an interaction effect on the psychological security and academic achievement of the students. The research method used was descriptive-comparative. A total of 266 respondents, whose ages ranged between 13 to 17 and were all in high school were the respondents in the study. Half of the total number of respondents (133) were from father-present families, the other half from father-absent families. The instruments used were the Personal Information Sheet (PIS) and the Filipino Self-Appraisal Inventory (FSAI) by Evangelista. The Filipino Self-Appraisal Inventory was designed by Dr. Salud Evangelista (1986) to assess the psychological security level of Filipino high school and college students. The inventory is composed of fifty items, thirty items which assessed one's view of self and seventeen assessed one's perception of the other's view of the individual. FSAI's validity is reflected in its high reliability (r=.92 at 0.0001 level) and its moderately high yet significant (p=0.0001) correlation with Maslow's Security/Insecurity inventory (r=-.67). To assess the academic achievement level of the students, the grade point average of the school year 1990-91 was used. The researcher employed the analysis of variance (ANOVA).Results showed that:1. There was a significant difference in the security level F (1,262) = 11.55 p.01 of the father-present students compared to the father-absent students. The security level of the father-present students is higher than the father-absent students (M2. There was a significant difference in the academic achievement level of the father-present students (M=85.18) compared to the father-absent students (M=83.85), F(1,262) = 6.37 p.01. These scores reflected average level of academic achievement.3. The presence or absence of the father has an effect on the security level of the students as well as on their academic achievement. Combining the two factors, group (presence or absence of father) and gender show no significant interaction effect on the security and academic achievement levels of the students.